Evaluation of safety and tolerability of a rush up-dosing allergen-specific immunotherapy with grass pollen, birch, hazel, and alder allergoid in children with allergic rhinoconjunctivitis, with or without asthma. - Traina, Giovanni; Martelli, Alberto; Barberi, Salvatore; Licari, Amelia; Marseglia, Gian Luigi; Tosca, Maria Angela; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2021)
BACKGROUND Usually, the number of injections required to achieve the maintenance dose in subcutaneous immunotherapy (SCIT) is relatively small for some of the currently used allergens, but this may still be uncomfortable for patients, thus compromising adherence and compliance. OBJECTIVE The purpose of this study was to evaluate the safety and tolerability of a dose acceleration of a conventional induction schedule using an allergoid extract of grass pollen, birch, hazel, and alder, needed to achieve the ideal maintenance dose. METHODS In this open-label study, 34 patients with allergic rhinoconjunctivitis, with or without asthma, were treated with SCIT using an allergoid for grass pollen or birch or mix trees with an increase in accelerated induction dose comprising only 3 injections, one per week, compared to a conventional induction pattern in five injections (once a week). Safety determination was assessed by evaluating local and systemic adverse events. Tolerability was evaluated by patients and physicians who performed the treatment. RESULTS No treatment-related adverse events were observed in any of the patients undergoing rush SCIT. No local reactions, no systemic reactions of any degree (WAO Grade) have been observed. Tolerability has always been rated as very good by both patients and physician. CONCLUSIONS The induction phase, needed to achieve the monthly maintenance dose for a pollen extract, can be greatly accelerated, ensuring a tolerability comparable to that of the conventional schedule.